Riak in Dayak Maanyan Ritual Tradition (An Ethnolinguistics Study) - Dwiani Septiana; Riyadi Santosa; Sumarlam Sumarlam (Institut Agama Islam Negeri (IAIN) Kendari, 2019)
Riak is a part of the ritual language in Dayak Maanyan ritual tradition, and functioning as a notification about stages of the ritual that are being and will be conducted by the master of the ritual. This study attempted to describe the form of riak through ethnolinguistics study. This study used ethnography research method. The primary data of this study were obtained from riak delivered by wadian in the traditional rituals of the Dayak Maanyan community in Paku Beto village, Paku sub-district, East Barito district, Central Kalimantan province. They were collected through observation and interview during January and April 2019. Findings of the study indicate that each riak mostly consists of four lines, in which the first two lines aim to prepare rhyme and rhythm in order to ease audiences understanding. This first two lines, in the beginning, are an illustration of the culture and the natural or environmental conditions in which the Dayak Maanyan community lives. Meanwhile, the second two lines are the purpose or content of riak that reveal the purpose of the Wadian in the ceremony. Some forms of word use in riak are morphologically different from its usage in the daily DM language. Those differences are the use of affix -i, clitic -ni, and particle sa, in order to give senses of beauty to riak utterances. Regarding the use of words, phrases, and sentences in riak utterances, there are found many descriptions about nature, living environment, habit, and local culture of the Dayak Maanyan community. This use clarifies that the community culture can affect language use.